Dengue coinfection in a case of enteric fever: a diagnostic and therapeutic dilemma (Bangladesh Journal of Medicine, 2018)
Presence of coinfection may make the otherwise straightforward presentation, diagnosis and management of the either disease complicated. Dengue and enteric fever coinfection is uncommon, though as a single disease both are common in tropical countries. Here, coinfection by dengue and enteric fever has been described in a 14-year-old boy residing in the tropic. Diagnosis of dengue was suggested by positive serological tests, and Salmonella paratyphi A was isolated by blood culture. Presence of enteric fever presumably protracted the course of illness by dengue fever. The patient was managed successfully by intravenous ceftriaxone, along with supportive care. So, the physicians practicing in the endemic region should have high degree of suspicion while dealing with the febrile patients in clinical practice.Bangladesh J Medicine Jul 2017; 28(2) : 100-103